Determinan Pemanfaatan Layanan Kesehatan Peserta BPJS Penerima Bantuan Iuran di Puskesmas Piyeung Kabupaten Aceh Besar 2024 - Nira Una; Fahmi Ichwansyah; Mira Gusweni (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Piyeung Health Center is recorded as the health center with the 5th lowest number of visits out of 28 health centers in Aceh Besar District. This is a concern because, although Piyeung Health Center has provided health services for BPJS Kesehatan participants in the PBI category, the low number of visits indicates that there are obstacles that hinder the optimization of the use of these services. This study aims to see the factors that cause the low number of visits at Piyeung Health Center. This study used a quantitative design with a cross-sectional approach. The study population was 3,394, and samples were taken using the accidental sampling technique of 100 respondents. Data analysis was carried out using the Chi-square test using SPSS version 30 with a significance level of 95%. The results of the univariate analysis showed that 88.0% of respondents had a good level of knowledge, 71.0% of respondents had easy accessibility, and 80.0% of respondents reported good health facilities. Meanwhile, 77.0% of respondents considered the actions of officers to be less than good, and 57.0% of respondents felt good family support. Bivariate analysis showed that officer actions (p-value 0.044), accessibility (p-value 0.002), and health facilities (p-value 0.006) had a significant relationship with the utilization of health services, while the level of knowledge (p-value 0.140), employment (p-value 0.222) and family support (p-value 0.078) did not show a significant relationship with the utilization of health services.